Analysis of EMG based Arm Movement Sequence using Mean and Median Frequency - B. N. Cahyadi; Wan Khairunizam; M. Nor Muhammad; Zunaidi Ibrahim; S.H. Majid Majid; Mohd Rudzuan Mohd Nor; Shahriman Abu Bakar; Zuradzman Mohamad Razlan; W. A. Mustafa (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
This paper present the studies of analysis arm movement sequence which dedicated for upper limb rehabilitation after stroke. The recovery of the arm could be optimized if the rehabilitation therapy is in a right manner. Upper limb weakness after stroke is prevalent in post-stroke rehabilitation, many factors that can deficit muscle strength there are neural, muscle structure and function change after stroke. Rehabilitation process needs to start as soon as after a stroke attack, repetitive and conceptualized. On the other hand monitoring of muscle activity also need in the rehabilitation process to evaluate muscle strength, motor function and progress in the rehabilitation process. The objective of this research is to analysis arm movement sequence using the feature frequency domain. In this study deltoid, biceps and flexor carpum ulnaris (FCU) muscles will be monitored by surface electromyography (sEMG). Five healthy subjects male and female become participants in data recording. Mean frequency (MNF) and median frequency (MDF) domain are two signals processing technique used for arm movement sequence analyzing. The analysis result showed that MNF is better than MDF where MNF produced higher frequency than MDF from each segment. From the data analysis, this movement sequence design more focuses on deltoid and FCU muscles treatment. This movement sequence has five condition movements. First undemanding, second difficult, third moderate, fourth moderate and the last cool-down movements. The best movement sequence minimum has four condition movements warming up - moderate - difficult - cool-down.